Gary Hall Jr's Full Breathing Stroke at 60 m of His 100 m Leg of the 4 x 100 m Free Relay Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S. (1997)
Video pictures (15 frames) and the explanations concerning Gary Hall Jr's Full Breathing Stroke at 60 m of His 100 m Leg of the 4 x 100 m Free Relay Gold Medal Race at the Atlanta Olympic Games 1996. Conclusion: The long arm position during propulsion of the crawl stroke sprinter provides a greater radius of rotation and therefore, greater distal velocity for the arm. The sprinter's speed is assisted by this more difficult and exhausting long arm pull. Gary Hall, Jr's obvious stretch forward under the water provides an opportunity for his arm's propulsive surface to create force over the longest distance possible. That contributes to his propulsion achieving the greatest possible amount of body acceleration. To be able to achieve the stroke rate and propelling surface velocity that is needed to be a top sprinter, the shoulder rotation is less in magnitude than is seen in distance swimmers. That is most likely because such rotations are relatively slow, particularly since they involve stopping to change rotational direction. There is insufficient time to perform any larger movement. At least the latter half of the arm-propulsion phase is achieved with the shoulder being rotated upward which refutes the popular misconception that crawl swimmers perform as much as possible on their side.